Implementation of Deep Learning on Improving Emotional Intelligence and Learning Motivation of Fifth Grade MI Students - Virdayasa, Lira; Mappanyompa, Mappanyompa; aqodiah, Aqodiah (Yayasan Pendidikan Bima Berilmu, 2026)
This study is limited by the lack of empirical research examining the application of deep learning in madrasahs with an emphasis on the emotional and motivational aspects of students. Previous studies have generally focused more on cognitive learning outcomes, so the effects of deep learning on emotional intelligence and learning motivation have not been widely explored. This study aims to examine the relationship and influence of deep learning on emotional intelligence and learning motivation. The method used is a quantitative approach with a correlational design. The research subjects involved 31 respondents consisting of students and teachers as supporting respondents. Data collection was carried out using a five-point Likert scale questionnaire with 18 statements. Data analysis was performed using JASP software through descriptive statistics and multiple linear regression techniques. The results showed that deep learning had a significant effect on emotional intelligence and learning motivation, as indicated by a significance value of < 0.05 and an R² value of 0.897. These findings confirm the novelty of the research in integrating deep learning with the strengthening of emotional and motivational dimensions in the context of madrasahs, and provide implications for the development of more comprehensive learning.